2019
DOI: 10.2147/cmar.s197749
|View full text |Cite
|
Sign up to set email alerts
|

<p>An efficient method that combines the ThinPrep cytologic test with E6/E7 mRNA testing for cervical cancer screening</p>

Abstract: Background: Cervical cancer is strongly associated with persistent human papillomavirus (HPV) infections. The ThinPrep cytologic test (TCT), HPV DNA detection, and E6/E7 mRNA testing are widely used to screen for cervical abnormalities. Purpose: This study aimed to find a suitable method for cervical cancer diagnosis (but not for cervical cancer distant metastasis), especially among women whose TCT results are atypical squamous cells of undetermined significance (ASCUS) or wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
10
2
Order By: Relevance
“…In this study, the positive rate of HPV DNA assay was 85.3%, which was much higher than that of the HPV E6/E7 mRNA test (61.6%).This relatively high percentage of HPV DNA infection in cases with positive cervical cytology is consistent with some previously published studies [22,23,27].There was an association between E6/E7 mRNA expression and histology (OR = 106.12) [28]. Data analysis from our study showed an association between the results of HPV E6/E7 mRNA, histological diagnosis, and the TCT grade.The positive rate of HPV E6/E7 mRNA and histological diagnosis increased with the upgrade of TCT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the positive rate of HPV DNA assay was 85.3%, which was much higher than that of the HPV E6/E7 mRNA test (61.6%).This relatively high percentage of HPV DNA infection in cases with positive cervical cytology is consistent with some previously published studies [22,23,27].There was an association between E6/E7 mRNA expression and histology (OR = 106.12) [28]. Data analysis from our study showed an association between the results of HPV E6/E7 mRNA, histological diagnosis, and the TCT grade.The positive rate of HPV E6/E7 mRNA and histological diagnosis increased with the upgrade of TCT.…”
Section: Discussionsupporting
confidence: 91%
“…There are many studies on the performance of HPV E6/E7 mRNA test in diagnosing cervical diseases. Some reports have suggested that HPV E6 / E7 mRNA test is more sensitive and speci c than the HPV NDA test [22][23][24]. It has also been suggested that the HPV E6/E7 mRNA test is only more speci c than the HPV DNA test,having no difference in sensitivity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the full-text of the 20 articles were reviewed, and different reports of the same clinical study and articles inconsistent with the purpose of this study were excluded. Ultimately, a total of 5 studies were included in the study (11)(12)(13)(14)(15). All the retrieval and screening processes were completed independently by 2 evaluators, and any differences in opinions were resolved through internal discussion (Table 1).…”
Section: Literature Retrieval Results and Included Research Character...mentioning
confidence: 99%
“…In this study, we analyzed 1,616 patients who were positive for HPV16/18/52/58 alone with TCT normal, with pathological findings suggestive of normal and inflammatory conditions accounting for 64.89%–78.51%, in line with a TCT specificity of 58%–76% ( 13 ). HPV screening can compensate for the lack of liquid-based cytology and can be combined with liquid-based cytology to improve sensitivity ( 14 ).The pathological findings suggest that HPV58-positive infection is more prevalent in patients with high-grade and above lesions than HPV52 positive and also higher than HPV18 positive. This is consistent with the Kaidar–Person study, which found that HPV58 has a 1.8-fold higher association with invasive cervical cancer than HPV52 ( 15 ).…”
Section: Discussionmentioning
confidence: 99%